Coverage and determinants of second-dose measles vaccination among under-five children in East Africa countries: a systematic review and meta-analysis - Alemu, Tewodros Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie; Mekonen, Enyew Getaneh; Ali, Mohammed Seid; Zegeye, Alebachew Ferede; Wassie, Mulugeta; Kassie, Alemneh Tadesse; Tekeba, Berhan; Gonete, Almaz Tefera (Frontiers in Public Health, 2024)
Background: One of the biggest breakthroughs of contemporary medicine is the measles vaccination. It is essential for elimination of measles. Understanding the magnitude and determinants of effective Second dose measles vaccination coverage is a critical task. Accordingly, we set out to check the best available evidence of the pooled second dose measles vaccination coverage among under five children in East Africa.We searched over electronic databases, including PubMed, Google Scholar, Cochrane, and others. Two reviewers separately carried out the Joanna Briggs Institute search, study selection, critical appraisal, and data extraction. A third party was involved in resolving the disagreement among reviewers. All seven studies included in this study; four in Ethiopia, two in Kenya, and one in Tanzania were cross-sectional studies, published in English language, with publication dates before November 29, 2023 and articles lacking full-text, intended outcome, and qualitative studies were excluded from the analysis. Microsoft Excel checklist was used to extract the data, then exported to STATA 11. I 2 , Funnel plots, and Egger's test were employed to measure heterogeneity and detect publication bias, respectively. A random effect model was used.The meta-analysis includes a total sample size of 4962 children from seven different articles. The pooled prevalence of second dose measles vaccination among under five children in East Africa was found to be 32. 22% (95% CI; (18.82, 45.63) and significant factors were: birth order 1.72(OR= 95% CI: 1.32, 2.23), information about Measles-Containing Vaccine two, 7.39 (OR= 95% CI: 5.21, 10.50), marital status 1.47 (OR= 95% CI: 1.05, 2.07), full immunization for other vaccines 2.17 (OR= 95% CI: 1.49, 3.17), and distance of vaccination site 3.31 (OR= 95% CI: 2.42, 4.53).The current study found that pooled prevalence of second dose measles vaccination coverage among under five children still very low. Also showed that birth order, distance of vaccination site, full immunization for other vaccines, marital status, and information about MCV were factors associated with second dose measles vaccination. This implies that there is a need for countries and their partners to act urgently to secure political commitment, primary health service expansion, increase vaccination coverage, and health education expansion.